Sampling Technique and Minimization of Inspection Errors in Leather Sorting - K. Logmen, Ayoub; K. Abusabah, Elnour; Suliman, Abdalla M. A. (Gezira Journal of Engineering and Applied Sciences, 2018)
Leather processing is one of the oldest industries. It involves processing of animals skins and hides for use in various products. The objectives of this study were to adopt a Sampling Plan Technique by comparison of various Sampling Plans in order to identify the best to be used in inspection process. This is to overcome human fatigue, to minimize the inspection time and to draw the Operating Characteristic Curve. A lot of 18000 pieces of wet blue goat skins for export was inspected for quality assurance to the standard quality level. These were set to be 10% & 5% for acceptable and rejects level by the supplier and customer respectively. Then various Acceptance Sampling Plans were compared then the probability of acceptance for lot quality level was evaluated using Operating Characteristic Curve. The results Showed that for quality assurance the best plan was when the lot size (N) was equal to  18000, the sample size (n) was equal to 350 and number of defects (c) was equal to 10. It is recommended that Acceptance Sampling Plan technique can be adopted by all Sudanese tanneries and related fields.